Pancreatic Fat Is Associated With Metabolic Syndrome and Visceral Fat but Not Beta-Cell Function or Body Mass Index in Pediatric Obesity. Issue 3 (March 2017) - Staaf, Johan; Labmayr, Viktor; Paulmichl, Katharina; Manell, Hannes; Cen, Jing; Ciba, Iris; Dahlbom, Marie; Roomp, Kirsten; Anderwald, Christian-Heinz; Meissnitzer, Matthias; Schneider, Reinhard; Forslund, Anders; et al.
Abstract : Objective: Adolescents with obesity have increased risk of type 2 diabetes and metabolic syndrome (MetS). Pancreatic fat has been related to these conditions; however, little is known about associations in pediatric obesity. The present study was designed to explore these associations further. Methods: We examined 116 subjects, 90 with obesity. Anthropometry, MetS, blood samples, and oral glucose tolerance tests were assessed using standard techniques. Pancreatic fat fraction (PFF) and other fat depots were quantified using magnetic resonance imaging. Results: The PFF was elevated in subjects with obesity. No association between PFF and body mass index-standard deviation score (BMI-SDS) was found in the obesity subcohort. Pancreatic fat fraction correlated to Insulin Secretion Sensitivity Index-2 and Homeostatic Model Assessment of Insulin Resistance in simple regression; however, when using adjusted regression and correcting for BMI-SDS and other fat compartments, PFF correlated only to visceral adipose tissue and fasting glucose. Highest levels of PFF were found in subjects with obesity and MetS. Conclusions: In adolescents with obesity, PFF is elevated and associated to MetS, fasting glucose, and visceral adipose tissue but not to beta-cell function, glucose tolerance, or BMI-SDS. This study demonstrates that conclusions regarding PFF and its associations depend on the body mass features of the cohort. Abstract : Supplemental digital content is available in the text.